Building an environmentally conscious generation: The Kidztainia 3.0 initiative in plastic waste management at SDN Cihuni III - Lolita, Theresia Lavietha Vivire; Tjokrodinata, Charlie; Valery, Shannon (Universitas Muhammadiyah Magelang, 2025)
The Kidztainia 3.0 initiative at SDN Cihuni III was designed as an innovative solution to enhance environmental awareness and sustainable waste management behavior among elementary school students. This program aimed to improve students' knowledge, skills, and commitment towards responsible plastic waste management. Implemented over six weeks at the end of 2023, the initiative involved students, teachers, and community members through three main approaches: (1) interactive narrative-based environmental education, (2) practical skills training in waste sorting and recycling drop-box management, and (3) intergenerational collaboration in environmental clean-up activities. Program evaluation showed a significant increase in students' knowledge regarding plastic types (85% improvement in classification ability) and enhanced commitment to sustainable practices. The success of Kidztainia 3.0, supported by the Pentahelix model (academia, industry, community, government, media), demonstrates the potential of school-based service-learning programs in supporting the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 and SDG 12, and provides a replicable model for other urban school contexts.